Accuracy in contests: Players' perspective - Mustafa Yildirim (Stockholm School of Economics, The Economic Research Institute (EFI), 2013)
We propose a political theory for the slow adoption of technology in sports and other contests. We investigate players' preferences for new technology that improves contest accuracy. Modeling accuracy as the elasticity of "production" in a standard Tullock contest, we show that players may be against higher accuracy if heterogeneity among them is:(1) sufficiently low; (2) moderate but the initial accuracy is low; or (3) high but the initial accuracy is high. We apply our results to the recent adoption of goal-line technology by major European soccer leagues.
Keywords: C72; D44; D72; 330; contest accuracy; politics; slow technology adoption; goal-line technology